A case report of spontaneous umbilical enterocutaneous fistula resulting from an incarcerated Richter's hernia, with a brief literature review. Issue 1 (December 2017) - Chen, Wei; Liu, Lei; Huang, Hui; Jiang, Mianxu; Zhang, Tao
Abstract Background Richter's hernia is a high-risk ischaemic gastrointestinal disorder that is typically diagnosed in a delayed manner due to a lack of obvious symptoms. Spontaneous umbilical enterocutaneous fistula (ECF) resulting from an incarcerated Richter's hernia is extremely rare. Case presentation A 62-year-old female presented with a chief complaint of recurrent umbilical region infection for the preceding 20 months with no symptoms of ileus. Preoperative CT and fistulography revealed an incarcerated Richter's hernia complicated by an ECF. Exploratory laparotomy revealed a loop of the distal ileum adherent to the umbilical region that was retrieved back into the abdominal cavity. Side-to-side ileo-ileal anastomosis was performed using a 75 mm linear stapler to remove the affected ileum segment. The internal hernia ring was closed using plication sutures instead of via mesh repair due to the patient's small defect and infection risk. Conclusion Richter's hernia can be observed at any age but is particularly common in frail, elderly patients. This nonspecific clinical and laboratory findings of this condition are associated with a high misdiagnosis rate, resulting inrelatively high mortality. Abdominal CT and gastrointestinal imaging are recommended if Richter's hernia is suspected. Timely surgical intervention is crucial for reducing mortality and improving prognosis.